NAFKAH IDDAH? WAJIB ATAU TIDAK? Is iddah maintenance obligatory or not? - Nazwa Azzahra Zoelva Manshur; Khairani Bakri (Reformasi Hukum Trisakti, 2025)
Marriage is a physical and mental bond between a man and a woman as husband and wife for eternity. However, in practice many marriages end in divorce. One of the consequences of divorce is the provision of iddah maintenance. Iddah maintenance is the maintenance that must be given by the former husband to the divorced ex-wife, this is as required and regulated in religious provisions and laws in Indonesia. These provisions obligate a husband to provide iddah maintenance. However, in its implementation in the community, some ex-husbands provide iddah maintenance, but some others do not provide iddah maintenance. So that the problem is how is the implementation of the provision of iddah nafkah after the gugat talak study of decision 4175/Pdt.G/2019/JS? The result and conclusion is based on the decision, Maulana did not fulfill the provision of iddah maintenance to his ex-wife Aisyah, where Maulana's actions violated court decision No. 4175/Pdt.G/2019/PA.JS and also the provisions of the Al-Quran and existing legislation in Indonesia.